Factor model of motor function in boys junior - Мірошниченко, Д. Т. (Physical Education Theory and Methodology, 2014)
The aim — to determine the factor model of motor function in boys junior. Methods and organization studies. The study used research methods such as analysis of the scientific and technical literature, pedagogical supervision, testing motor training, probabilistic approach to the assessment of the learning process, methods of mathematical statistics. In the study involved boys Class 2 — 38 people, Class 3 — 42 people, Class 4 — 48 people. Conclusions. In the factor model of motor function in males are: learning and development of motor skills (second class); learning and development of power abilities (third grade); learning and development of power and coordination abilities (fourth class). The most informative for assessment of motor function in boys with: second class - the level of training of acrobatic exercises (0.848; 0.774; 0.809); third grade - the level of development of the security capabilities: test "Pulling in mixed Wiese on the rope (times)" (0.941), the level of training exercises: "The rise of revolution in focus stroke one" (0.910), "Most of the prone position" (0.860) ; fourth grade - the level of training exercises "Climbing the rope in 2 hours" (0.939), "Climbing the rope in 3 hours" (0.939), "The rise of revolution in focus stroke one" (0.745), and the test results: № 7 " Pulling in mixed Wiese on the rope »(0,787), № 10" Time saving sustainable position - stand on one leg with eyes closed "(0.723).